Análisis Financiero en la Empresa “Distribuidora Torres Disfertor Cia Ltda” de la Ciudad de Loja, Periodos 2020-2021. - Guamán López, Ana Gabriela (2025)
The Curricular Integration Work entitled FINANCIAL ANALYSIS IN THE COMPANY “DISTRIBUIDORA TORRES DISFERTOR CIA LTDA” OF THE CITY OF LOJA, PERIOD 2020-2021, was developed in order to evaluate the economic-financial performance of the company, through vertical and horizontal analysis and indicators, which allowed to evaluate the liquidity, activity, profitability and indebtedness. Different methods were applied, such as scientific, deductive, inductive, analytical, synthetic and research techniques such as observation, interview and information gathering, which facilitated the realization and fulfillment of the proposed objectives. The vertical analysis of the financial statements for the periods 2020-2021 was carried out, where it was determined that during the year 2021 the Current Assets increased 34.18% due to the advance payment to its suppliers, and its long-term debts grew 38.42% due to the existing obligations with financial institutions. Regarding the economic structure, it was evidenced that the account with the highest representation in the Income from Ordinary Activities are bonuses, monthly incentives, reimbursements and discounts equivalent to 84.28%; regarding the costs related to the operating part of the company, they are mainly structured by the cost of sales and production account, representing 35.67%; finally the item with the highest representation in the expenses are the Operating Lease Expenses with a percentage equivalent to 23971.88%. Regarding the financial indicators, it was determined that the company has $1.29 cents in 2020 and $1.49 in 2021 to pay its debts, that is, it is not in a position to pay without having to resort to its inventories, in 2020 its inventory has rotated in 356 days and in 2021 in 183 days, it is good because it does not accumulate its merchandise for a long time. For the year 2021 the company has 89% of indebtedness and there is a risk of not being able to pay all of its debts, so a financial report was prepared with the appropriate conclusions and recommendations that allow making the right decisions.